2018
DOI: 10.1002/job.2331
|View full text |Cite
|
Sign up to set email alerts
|

Teams as boundaries: How intra‐team and inter‐team brokerage influence network changes in knowledge‐seeking networks

Abstract: Summary What role does an ego's brokerage location—within a team (intra‐team) or outside the team (inter‐team)—play in the evolution of an instrumental knowledge‐seeking network in terms of both proximal (i.e., within the team) and distal (i.e., outside the team) tie formation and tie decay? We address this question by drawing on literature about social networks, brokerage, and teams. We use temporally separated data from 302 students embedded in 97 teams to test our hypotheses about the impacts of intra‐team … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 75 publications
(129 reference statements)
0
15
0
Order By: Relevance
“…Further, the leaders of higher performing teams tended to be well-connected in both the internal team network as well as network external to the team. Balkundi et al (2019) Quantitative Team Whereas intrateam brokerage was negatively associated with tie decay outside of the team, it was positively associated with tie decay inside of the team and negatively associated with the formation of new ties both within and external to the team. Balogun et al (2005) Qualitative System The authors advanced the concept of 'boundary-shaking' which refers to individuals' use of their knowledge of social networks within and between organizations to create new networks and/or redefine old ones in order to gain support for their change initiatives.…”
Section: Discussionmentioning
confidence: 98%
“…Further, the leaders of higher performing teams tended to be well-connected in both the internal team network as well as network external to the team. Balkundi et al (2019) Quantitative Team Whereas intrateam brokerage was negatively associated with tie decay outside of the team, it was positively associated with tie decay inside of the team and negatively associated with the formation of new ties both within and external to the team. Balogun et al (2005) Qualitative System The authors advanced the concept of 'boundary-shaking' which refers to individuals' use of their knowledge of social networks within and between organizations to create new networks and/or redefine old ones in order to gain support for their change initiatives.…”
Section: Discussionmentioning
confidence: 98%
“…Along these lines, recent research has examined the effects of team network structures and leaders' social network positions within these structures (i.e., internal network; Balkundi et al, 2019;Mehra et al, 2006). Because leaders can influence, and are influenced by, the patterns of relationships among themselves and their team members, internal networks are critical for information exchange, developing interdependence, and leadership effectiveness (Balkundi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, meta-analytic results show that teams whose leaders are more central in the team's informal networks have higher team viability and performance (Balkundi & Harrison, 2006). However, leaders' networks are also of particular interest when considering the broader community to which a leader is connected (i.e., external networks; Balkundi et al, 2019;Carter et al, 2020;Mehra et al, 2006). Frontline leaders serve as linchpins by occupying network positions that bridge upper level executives and lower level employees, facilitating relationship-building and information exchange with superiors, peer leaders, and subordinates throughout an organization (Mehra et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, scholars have carried out some researches on the relationship among the cooperation, innovation, and knowledge flow. Jiang et al [19] proposed that partner trustworthiness had a positive role in the knowledge acquisitioncan and had different effects on the knowledge leakage under different alliance regimes; Cheong et al [20] researched the relationship between knowledge flow and the purpose of expatriate assignments and found that different enterprises had different knowledge flow strategies; Gaur et al [21] explored the cross-border flow of knowledge and proposed a comprehensive knowledge management framework; Christian and Uschi [22] explored the occurrence of superior in-cremental innovation performance based on the a knowledge creation (KC) system which was integrated by knowledge stock and flow; Lo [23] used a multidimensional knowledgeflow model to explore the knowledge flow across different stakeholders in an organization; Zhao et al [24] established a dynamic system evolution model and analyzed the relationship between knowledge absorption capacity, knowledge potential, and knowledge transfer capacity under different incentives intensities, they found that incentive mechanism could promote the evolution of strategic alliance innovation; Li et al [25] explored the relationship among knowledge flow of multimedia information, alliances and clusters, they found that similarity, complementarity and spillage of knowledge were conducive to the formation of the alliance; Zhou and Wu [26] used the dynamic model of knowledge flow in a complex network to explore the transmission rate of the knowledge in the network, they considered that the average degree of the network, the number of enterprises involved in the transfer, and the effective transmission rate of the knowledge had significant influences on the efficiency of the knowledge flow; in addition, other scholars explored the knowledge flow in teams [27], workplace [28,29], citations of articles [30], universities [31] and supply chain [32]. Above existing studies explored the knowledge flow from different perspectives and levels based on the static perspective mostly, few scholars explore the phenomenon of knowledge flow in the process of senior executives' cooperation.…”
Section: Introductionmentioning
confidence: 99%